Bantahan Atas Hexagon Fraud Theory - Sudrajat Martadinata; Eka Haryanti; Fadli Faturrahman (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This paper aims to understand reality in the private sector. The reality that we encounter is very strong in providing a rebuttal to the Hexagon Fraud Theory. Taken from a movie scene entitled In The Heart of The Sea (2015). Using a dramaturgical research method with a performance approach. The results of this study enrich the diversity of fraud theory which provides an antithesis of even the latest fraud theory. Various factors that cause fraud are mentioned in various theories. All of them are perfectly refuted when we analyze the reality we encounter.